Relasi Kuasa Perkawinan Anak di Bawah Umur dalam Novel I Am Nujood, Age 10, and Divorced - Mirza Fathima Jauhar Kamalia (BUANA GENDER : Jurnal Studi Gender dan Anak, 2017)
Child marriage can be seen as an oppression that not all women in the world will experience it. It happens only in poor and traditional countries like in Yemen. Child marriage in Yemen is clearly described in me Nujood, Age 10, and the Divorce novel. Behind the phenomenon of child marriage, there are several relations of relationships that run it from generation to generation. This study aims to find the power relationships behind the marriage of my child that is Nujood, Age 10, and Divorce. This study uses qualitative methods and readings as data collection. The results of this study indicate that there are three power relationships behind the marriage of children: child marriage as a form of preservation of tradition from generation to generation, marriage of children as a solution to the difficulties of the family financial condition, and marriage of children as a form of preservation of illiterate women.